Investigating the Democratic Potential of Temporary Uses in Urban Redevelopment Projects. - Parker, Peter; Vogel, Nina; Diedrich, Lisa (Palgrave Macmillan, 2019)
The authors start out by shedding critical light on temporary urbanism, one of the latest fashions among urban planners and politicians, emphasising how temporary use can both reinforce hegemonies and enable alternatives. They suggest how the former can be avoided in pursuit of the latter.
Keywords: Stadtforschung; Stadttheorie; Konflikt; Raum; Urbanität; Zwischennutzung; Partizipation; Nutzungsänderung